2012
DOI: 10.1371/journal.pone.0035209
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Age-Based Hunting Regulations for African Leopards

Abstract: In species in which juvenile survival depends strongly on male tenure, excessive trophy hunting can artificially elevate male turnover and increase infanticide, potentially to unsustainable levels. Simulation models show that the likelihood of safe harvests can be improved by restricting offtakes to males old enough to have reared their first cohort of offspring to independence; in the case of African leopards, males were ≥7 years old. Here, we explore the applicability of an age-based approach for regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 31 publications
(49 reference statements)
0
86
0
Order By: Relevance
“…Finally given the difficulty in aging leopards (Balme et al. 2012) documented by Ray (2011) in nearby Luambe National Park and the high potential for harvesting female leopards in trophy hunts (Spong et al. 2000), the impacts of past leopard harvests, particularly those that did not adhere to sex‐ or age‐based limits (Balme et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally given the difficulty in aging leopards (Balme et al. 2012) documented by Ray (2011) in nearby Luambe National Park and the high potential for harvesting female leopards in trophy hunts (Spong et al. 2000), the impacts of past leopard harvests, particularly those that did not adhere to sex‐ or age‐based limits (Balme et al.…”
Section: Discussionmentioning
confidence: 99%
“…2000), the impacts of past leopard harvests, particularly those that did not adhere to sex‐ or age‐based limits (Balme et al. 2012), are likely to persist for several years. Despite these potential problems, our data provide no evidence that differences in management during the hunting moratorium directly affected leopard mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leopard trophy size was also assessed by estimating the ages of leopards displayed on outfitter's online trophy galleries. Balme et al (2012) demonstrated that leopards could be accurately aged using morphological characteristics (e.g. dewlap size, facial scarring, ear wear) featured in photographs.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly managed trophy hunting is a particularly important source of mortality in leopard populations, as leopards have naturally high rates of infanticide (e.g. Balme, Hunter, & Braczkowski, 2012; 40% in a protected population in the SabiSands). This is exacerbated by trophy hunting and may cause rapid population declines by artificial turnovers of adult males (Balme et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%